Organomercury Nucleic Acids: Past, Present and Future - Ukale Dattatraya; Lönnberg Tuomas (WILEY-V C H VERLAG GMBH, 2025)
Synthetic efforts towards nucleosides, nucleotides, oligonucleotides and nucleic acids covalently mercurated at one or more of their base moieties are summarized, followed by a discussion of the proposed, realized and abandoned applications of this unique class of compounds. Special emphasis is given to fields in which active research is ongoing, notably the use of Hg-II-mediated base pairing to improve the hybridization properties of oligonucleotide probes. Finally, this minireview attempts to anticipate potential future applications of organomercury nucleic acids.